Frequency and distribution of foot lesions identified during cattle hoof trimming in the Province of Antioquia, Colombia (2011–2016) (2018)
ABSTRACT: Lameness is a severe welfare problem in cattle and has a detrimental effect on longevity, productivity, and reproductive performance. This study aimed to describe the frequency and distribution of foot lesions in cattle using hoof trimming records over a period of 6 years in the Province of Antioquia (Colombia). The data collection instrument enabled differentiation between limbs, digits, and views. The Claw Lesion Identification in Dairy Cattle brochure was the reference for foot lesion identification. A total of 1814 foot lesions observations, recorded from 1120 cows in 71 herds, were analyzed and 11 different foot lesions were identified. Non-infectious foot lesions were more common tan infectious (94.4 vs 5.6%). White line disease was more frequently observed in the hind limbs (79.6%) compared to the front limbs (20.4%), and more frequent in medial claws of the front limbs (70.3%) compared to lateral claws (29.7%). In hind limbs, the lateral claws were more commonly affected (65.7%) compared to the medial claws (34.3%). Claw zone 3 was affected in 61.3% of the cases, followed by zones 2 (21.7%) and 1 (17%). Although our data are from a limited area of the country, they are consistent with published and anecdotal reports of foot lesions in cattle in Colombia and worldwide. Our results suggest that there is need for additional prospective research under Colombian dairy cattle management conditions to better understand the lameness and benefit of trimming intervention.